BRAND AWARENESS AND BRAND IMAGE OF DECISION MAKING ON UNIVERSITY (Jurnal Manajemen dan Kewirausahaan, 2016)
Universities are currently facing many challenges as institutions of higher education providers, espe-cially in obtaining numbers of students. The purpose of the study is to examine the effect of brand awareness on brand image, the effect of brand image on perceived value, the effect of perceived value on satisfaction, the effect of brand image on satisfaction, the effect of satisfaction on loyalty. Data collection methods are obtained from 200 samples of students in Jambi (primary data) with an analysis of Structural Equation Model Lisrel 8.80. The findings of this research are four hypothesis take positive and significant effect where Satisfaction has the most effect. However, it did not find any influence of brand image on satisfaction.